PENGARUH KUALITAS LAYANAN DAN NILAI TERHADAP KEPUASAN SERTA DAMPAKNYA TERHADAP LOYALITAS - Desi Maya Sulistyowati, 09.05.51.0098 (Students Journal of Economic and Management, 2013)
The purpose of this study was to measure the level of customer satisfaction and loyalty by examining variables - variables that affect the identification of customer satisfaction and loyalty at Bank BNI Syariah Branch Office Semarang . After a review of related literature, in this study determined significant variables that allegedly affects customer satisfaction and loyalty, which is the variable quality of service that includes dimensions of physical evidence ( tangibles ), reliability (reliability ), security (assurance ), responsiveness (responsiveness ), and empathy ( empathy ) and variable customer value can be seen as a basis for the development strategy of customer satisfaction leads to loyalty. In this study , researchers used purposive sampling and obtain a sample of 100 customers of Bank BNI Syariah Branch Office Semarang. The data were analyzed using factor analysis to test the validity of the item in question , and the formula Croanbach s Alpha to test the reliability of the instrument. The data analysis technique used in this study was SPSS for Windows 16.0, which is used to test the 5 ( five ) hypothesis that has been cultivated. And hypothesis testing results showed a positive and significant relationship between the quality of services that include physical evidence (tangibles), reliability (reliability), security (assurance), responsiveness (responsiveness), and empathy (empathy), on customer loyalty with customer satisfaction mediated. Also found a direct relationship between the positive and significant customer value with customer satisfaction and customer loyalty. The results of calculations for model testing showed acceptable results using Regression Analysis and Path Analysis. Keywords : Service Quality , Customer Value , Customer Satisfaction and Customer Loyalty